Approaches to Treatment of Rhinosinusitis in Children - O.Ye. Abaturov; O.M. Gerasymenko; L.L. Petrenko; V.O. Dytyatlovsky; N.M. Lybenko (Zaslavsky O.Yu., 2012)
The paper presents the main mechanisms of development, clinical manifestations and approaches to the treatment of acute rhinosinusitis in children. The advantages of combined medication, which includes phenylephrine and chlorpheniramine maleate, are described.